Advance in renewable energy using piezoelectric power-harvesting devices - Ismail, Noorradiyah (2013)
This paper presents a designing piezoelectric harvesting energy device by having mechanical stressWhole system of the designing must be verified and validated through extensive experimental tests. The system structure consists of controller circuit that uses to simulate the system and show the amount of voltage. This generated electrical energy can be harvested using the principle of piezoelectric energy conversion. The propose design is divided into three categories, which are designing the prototype, electronic part and mechanical part. Designing proper mechanisms for exciting the piezoelectric device is necessary also proper electronic control circuits must be designed and modeled. It is used before implementing to the energy storage using a typical bettery. The project gives a new idea to develop a renewable energy as an electrical power system that can generate a power from having a lot of force from people moving so that they would not only depend on the hydro and coal power system.